Ironic festival brand co-creation - Suomi Kati; Luonila Mervi; Tähtinen Jaana (Elsevier Inc., 2022)
This paper embraces the daring use of ironic humor in brand co-creation in festival branding. Innovative branding is an aspiration in the growing festival business. This study explores a unique case: a festival that applies ironic humor in its brand co-creation despite the risks involved. The findings suggest that the use of ironic humor, when made inherent to a festival's brand identity, can increase stakeholders' attention to and awareness of the festival and attract positive media attention. Moreover, the use of ironic humor can prompt stakeholders on social media to share and co-create the festival's brand identity. The study contributes to the literature on festival brand co-creation by demonstrating the use of ironic humor to engage stakeholders in brand co-creation.